Health fund for poor = (The World Bank in Vietnam (WB), 2004)
The purpose of this Procurement Threshold Projects for Vietnam is to seek the approval of the country director to proceed with an umbrella restructuring to change the provisions for the Bank's review thresholds specified in the respective Development Credit Agreement (DCA) or Financing Agreement (FA) for the projects in the Vietnam portfolio listed in annex one. The specific change for which approval is sought through this project paper is to change the provisions for 'review by the association of procurement decisions' of DCA